Dopamine D1-like Receptors Regulate Constitutive, μ-Opioid Receptor-Mediated Repression of Use-Dependent Synaptic Plasticity in Dorsal Horn Neurons: More Harm than Good? - Aira, Zigor (J Neurosci, 2016)
The current study reports on a synaptic mechanism through which D1-like receptors (D1LRs) modulate spinal nociception and plasticity by regulating activation of the μ-opioid receptor (MOR). D1LR stimulation with agonist SKF 38393 concentration-dependently depressed C-fiber-evoked potentials in rats receiving spinal nerve ligation (SNL), but not in uninjured rats. Depression was prevented by MOR- but not GABA-receptor blockade. Neurons expressing the D1 subtype were immunopositive for met-enkephalin and vesicular glutamate transporter VGLUT2, but not for GABAergic marker vGAT. Nerve ligation was followed by increased immunoreactivity for D1 in synaptic compartment (P3) in dorsal horn homogenates and presynaptic met-enkephalin-containing boutons. SNL led to increased immunoreactivity for met-enkephalin in dorsal horn homogenates, which was dose-dependently attenuated by selective D1LR antagonist SCH 23390. During blockade of either D1R or MOR, low-frequency (0.2 or 3 Hz) stimulation (LFS) to the sciatic nerve induced long-term potentiation (LTP) of C-fiber-evoked potentials, revealing a constituent role of both receptors in repressing afferent-induced synaptic plasticity. LFS consistently induced NMDA receptor-dependent LTP in nerve-injured rats. The ability of MOR both to prevent LTP and to modulate mechanical and thermal pain thresholds in behavioral tests was preserved in nerve-ligated rats that were postoperatively treated with SCH 23390. D1LR priming for 30 min sufficed to disrupt MOR function in otherwise naive rats via a mechanism involving receptor overuse. The current data support that, whereas D1LR-modulated MOR activation is instrumental in antinociception and endogenous repression of synaptic plasticity, this mechanism deteriorates rapidly by sustained use, generating increased vulnerability to afferent input. SIGNIFICANCE STATEMENT The current study shows that dopamine D1-like receptors (D1LRs) and μ-opioid receptors (MOR) in the spinal dorsal horn constitutively repress the expression of synaptic long-term potentiation (LTP) of C-fiber-evoked potentials. Anatomical data are provided supporting that the D1 subtype regulates MOR function by modulating met-enkephalin release. Sustained neuropathic pain induced by spinal nerve ligation is accompanied by D1R and met-enkephalin upregulation, acquired D1LR-mediated antinociception, and a loss of endogenous repression of further synaptic plasticity. We show that the ability of MOR to oppose LTP is rapidly impaired by sustained D1LR activation via a mechanism involving sustained MOR activation.